2022
DOI: 10.5755/j01.ee.33.3.29652
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Active Labour Market Policies in the EU Countries for the Young Unemployed People and Implications for the Post-pandemic Period

Abstract: The Covid-19 pandemic has exposed vulnerability of young people in the labour market. Young people are faced with risks and an uncertain future, as well as changing the nature of labour markets. Active labour market policies are addressed as the main instrument to improve employment possibilities of young people in the light of the Covid-19 pandemic situation and its aftermath. This paper analyses the effectiveness of active labour market policies in reducing youth unemployment for the EU-26 Member States usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Despite tremendous efforts applied by the governments to support youth employment, some of the studies have shown ineffectiveness of ALMP. The research by Laura Juznik Rotar (2022) used macroeconomic panel data for the EU-26 Member States to analyze the effectiveness of active labour market policies in reducing youth unemployment. The results pointed to the ineffectiveness of active labour market policy in reducing youth unemployment in the EU-26 Member States.…”
Section: Risks and Prospects Of Youth Employmentmentioning
confidence: 99%
“…Despite tremendous efforts applied by the governments to support youth employment, some of the studies have shown ineffectiveness of ALMP. The research by Laura Juznik Rotar (2022) used macroeconomic panel data for the EU-26 Member States to analyze the effectiveness of active labour market policies in reducing youth unemployment. The results pointed to the ineffectiveness of active labour market policy in reducing youth unemployment in the EU-26 Member States.…”
Section: Risks and Prospects Of Youth Employmentmentioning
confidence: 99%
“…What is more, education researchers are aware that what young people think of themselves now can have long-term effects on how well they do as adults [1]. Therefore, the vulnerability of young people in job markets who are at risk due to the COVID-19 pandemic facing risky and uncertain future, as well as the continuing changes in the nature of the Labour market [2]. The following will take measures to increase employment for individuals, the government, and social media through the data of young people's employment psychology and problems, and the same employment-related problems facing in other countries besides China and their solutions.…”
Section: Introductionmentioning
confidence: 99%